Neuro-immune relationships at patients with chronic pyelonephrite and cholecystite. Communication 2. Correlations between parameters EEG, HRV and Phagocytosis - Andriy B Kul'chyns'kyi; Marta M Kovbasnyuk; Tetyana A Korolyshyn; Valeriy M Kyjenko; Walery Zukow; Igor L Popovych (Kazimierz Wielki University, 2016)
Kul'chyns'kyi Andriy B, Kovbasnyuk Marta M, Korolyshyn Tetyana A, Kyjenko Valeriy M, Zukow Walery, Popovych Igor L. Neuro-immune relationships at patients with chronic pyelonephrite and cholecystite. Communication 2. Correlations between parameters EEG, HRV and Phagocytosis. Journal of Education, Health and Sport. 2016;6(10):377-401. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.163221 http://ojs.ukw.edu.pl/index.php/johs/article/view/3957         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 21.10.2016.       Neuro-immune relationships at patients with chronic pyelonephrite and cholecystite. Communication 2. Correlations between parameters EEG, HRV and Phagocytosis   Andriy B Kul'chyns'kyi1, Marta M Kovbasnyuk2, Tetyana A Korolyshyn2, Valeriy M Kyjenko2, Walery Zukow3, Igor L Popovych2   1Communal Hospital, Truskavets', Ukraine  akul@i.ua 2Laboratory of Experimental Balneology, OO Bogomoletz Institute of Physiology NAS, Kyiv, Ukraine  i.popovych@biph.kiev.ua   marta.kovbasnyuk@yandex.ua 3Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland  w.zukow@ukw.edu.pl   Abstracts Background. Previously, we have shown that blood level of Leukocytes and parameters of Leukocytogram significantly modulated by electrical activity some structures of central and autonomic nervous systems. In this study, we set a goal to analyse the relationships between parameters of EEG and HRV, on the one hand, and the parameters of phagocytosis, on the other hand. Methods. In basal conditions in 23 men, patients with chronic pyelonephrite and cholecystite in remission, recorded EEG ("NeuroCom Standard", KhAI Medica, Ukraine) and HRV ("Cardiolab+VSR", KhAI Medica, Ukraine). In portion of venous blood estimated parameters of phagocytic function of neutrophils. Results. Revealed that canonical correlation between constellation EEG and HRV parameters form with Phagocytic Index 0,94 and 0,93 for E. coli and Staph. aureus respectively. However neural regulation Killing Index as well as Microbial Count significantly distinguished for Gram-negative and Gram-positive Bacteria: R form 0,99 and 0,84 versus 0,66 and 0,69 respectively. Integrated parameter Bactericidity Capacity of blood Neutrophills correlated with EEG and HRV parameters equally: R makes 0,89 and 0,93 respectively. Conclusion. Neutrophils phagocytic function subordinate modulation central and autonomic nervous systems. Keywords: HRV, EEG, Phagocytosis, Escherichia coli, Staph. aureus, correlations.